2017
DOI: 10.21037/tau.2017.06.09
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical management of recurrent urinary tract infections in women

Abstract: One in three women will experience a clinically significant urinary tract infection (UTI) by age twenty-four and almost half will have at least one in their lifetime. Recurrent UTIs (rUTIs) are defined as having greater than two infections in a 6-month period, or three infections over twelve months, with complete resolution for at least two weeks. These may be due to relapse from incomplete treatment (persistence) or re-infection (new source). It may be difficult to distinguish between the two, where the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 86 publications
0
16
0
1
Order By: Relevance
“…Similar observations were reported in the urine samples, globally. [15][16][17][18][19][20] Urinary tract infections are believed to be the second most predominant communitybased and nosocomial infections, worldwide. 21,22 These findings represent that urine and urinary tract environment demonstrate a higher prevalence of uropathogens due to the longer hospital stay, sexual activity, diabetes, hormonal imbalance, and genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported in the urine samples, globally. [15][16][17][18][19][20] Urinary tract infections are believed to be the second most predominant communitybased and nosocomial infections, worldwide. 21,22 These findings represent that urine and urinary tract environment demonstrate a higher prevalence of uropathogens due to the longer hospital stay, sexual activity, diabetes, hormonal imbalance, and genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-antimicrobial intravesical instillations such as hyaluronic acid and chondroitin sulfate have also been used [ 15 ]. During our literature research, we also identified other antimicrobials such as tobramicin, linezolid and vancomycin which have been used as IVA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, bladder instillations containing HA have been shown to reduce UTI episodes and pain30, 35, 36 with in vivo studies suggesting that HA treatment is associated with reduced bacterial growth 37. However, these are only used in cases of extremely unresponsive rUTIs 20. A recent clinical trial has reported the effects of HA combined with Propionibacterium acnes as a potential treatment to combat vaginal infections, functioning presumably by enhancing the immune system in the vaginal/vulval tissues 38.…”
Section: Discussionmentioning
confidence: 99%
“…In support of a role for oestrogen in the innate defence of the urogenital tract, topical, but not oral oestrogen treatments have proven successful in reducing infections with these effects mediated through the vaginal commensal populations and the urogenital innate defences 16, 17, 18, 19. However, because of the side effects, the use of topical vaginal oestrogen is not always appropriate for all women20 and hence its therapeutic potential in treating rUTIs is limited.…”
Section: Introductionmentioning
confidence: 99%